Comparative evaluation of immune response to secondary inoculation of sheep red blood cells in egg-type chicken - SAINI, SAMITA; CHAUDHARY, M L; BRAH, G S; BAJWA, I S (The Indian Journal of Animal Sciences, 2013)
Present study was conducted to evaluate humoral immune response of 3 White Leghorn (WL) and 2 Rhode IslandRed (RIR) strains to booster inoculation of sheep red blood cells. Immune response to sheep red blood cells wasmeasured as total, Mercapto-ethanol resistant (MER) and Mercapto-ethanol sensitive (MES) titre at 6, 10, 14 and 18days post secondary (booster) inoculation. Haemagglutination titre gives indication of total antibodies while MER andMES titre represented level of immunoglobulin G (IgG) and immunoglobulin M (IgM) respectively. The overall antibodyproduction was higher after booster inoculation when compared with birds not given booster. There were significantdifferences between the strains for response to booster, with WL being superior and differing significantly from RIRstrains. Thus RIR strains had lower level of antibodies against SRBC booster. Of WL selected strains PL1 had betterimmune responsiveness compared to PL2 and control except for MER level, which was higher in PL2. The overall peaktiter value was occurring during 6d PSI for total and MES titre and during 10d PSI for MER titre. The antibody titreafter booster inoculation first peaked during 6–10d PSI and then gradually declined. There were significant differencesbetween days PSI for total antibody titre in birds given and not given booster inoculation while MER and MES have nosignificant differences for days PSI.